(untitled) - Morais, Herbert V. (Philippines, 2004)
The handbook provides with a basic knowledge and understanding of the key international standars and best practices.
Keywords: Terrorism,Terrorism investigation,Khủng bố,Sự điều tra khủng bố; Finance,Tài chính